PERKEMBANGAN SOSIAL EMOSI PADA ANAK USIA DINI - Nazia Nuril Fuadia (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2022)
Abstract This study aims to describe the theory of social and emotional development of children so that child development is achieved optimally. This research uses literature study method. The data obtained were compiled, analyzed, and concluded to get a conclusion. The results of this study show that the development of social emotions is determined by two factors, namely internal factors, namely the human nature itself (humanistic theory) and external factors, namely the surrounding environment (Psychosocial theory). Children's social and emotional development is also obtained not only from the maturation process, but also from learning opportunities and responses from their environment. Social competence is determined by emotional competence. Children with good emotional intelligence tend to be socially competent individuals. Children who can control themselves and easily show affection to others will be easy to socialize with people around them. Therefore, the emotional and social devlopment of children develops well. so that they are ready for the next life.   Abstrak Penelitian ini bertujuan untuk mendeskripsikan teori perkembangan sosial dan emosi anak. Penelitian ini menggunakan metode studi literatur. Data yang diperoleh dikompilasi, dianalisis, dan disimpulkan sehingga mendapatkan kesimpulan. Adapun hasil penelitian ini bahwa perkembangan emosi sosial ditentukan oleh dua faktor yaitu faktor internal yaitu bawaan manusia itu sendiri (teori humanistik) dan faktor eksternal yaitu lingkungan sekitar (teori Psikososial). Perkembangan sosial dan emosi anak juga diperoleh tidak hanya dari proses kematangan, melainkan diperoleh dari kesempatan belajar dan respon dari lingkungannya. Kompetensi sosial ditentukan oleh kompetensi emosi. Anak dengan kecerdasan emosi yang baik cenderung menjadi pribadi yang kompeten secara sosial. Anak yang dapat mengendalikan diri dan mudah menunjukkan kasih sayang kepada orang lain maka akan mudah bersosialisasi dengan orang disekitarnya. Oleh karena itu, perkembangan emosi dan sosial anak berkembang dengan baik sehingga memiliki kesiapan dalam kehidupan selanjutnya.